Utilization of gadgets in interactive books based on Augmented Reality (AR) as a medium for the formation of noble morals in elementary school students - Mulyadi, Syifa Friscilla; Putri, Sifa Alya; Purnama, Wita; Amnasriyah, Aliyah; Reza, Sopian Muhamad; Parhan, Muhamad (FISIP UIN SGD Bandung, 2025)
The use of Augmented Reality (AR)-based interactive books is currently highly necessary, especially in the field of education. This is because books presented in AR format offer a more interactive, engaging, and effective way of learning for students. This study aims to analyze the skills of elementary school students in understanding the content of materials presented in AR-based interactive books, assess their validity and reliability, and evaluate the expert feasibility of the AR-based interactive book. The method used in this research is descriptive qualitative. The sample consisted of 20 elementary school students from a school in West Bandung Regency. The results of the study indicate that, overall, the AR-based interactive book developed is feasible for use. This conclusion is based on observation results, validity and reliability tests, and expert feasibility assessments. The material presented in this study, which is packaged in an AR-based interactive book, is still limited to the topic of the traits of prophets. Therefore, further development is needed to include a wider variety of topics. In addition, the AR packaging in this study is still limited to digitalizing the book and adding audio features via barcode scanning. Contribution: This article offers empirical evidence that AR integration can enhance student engagement and comprehension, particularly in teaching religious traits, while highlighting the potential for expanding AR applications to broader content areas in future research.